An investigation on role of salinity, pH and DO on heavy metals elimination throughout estuarial mixture - A. R. Karbassi; M. Heidari (Global Journal of Environmental Science and Management)
One of the most paramount processes that play a considerable role in reducing the concentration of heavy metals during estuarine mixing is flocculation. Not only does such a process cause a huge percentage of metals to come into the particulate phase, but also it provides ample nutrients for the aquatic life. In the present study, impact of such factors as salinity, pH and DO on flocculation of Cu, Zn, Pb, Ni, Cd and Mn throughout mixing of Chaluse River with Caspian Sea is investigated. The trend of flocculation of Pb (24.32%) < Zn (24.38%) < Cd (40.00%) < Cu (64.71%) < Ni (68.00%) < Mn (76.47%) reveals that among the studied elements Mn and lead experience minimum and maximum flocculation at diverse salinity regimes, respectively. Moreover, flocculation rate of studied metals fluctuates between 24.32 and 76.47 percent.  It is interesting to note that much of metal flocculation occurs at the very lower (less than 2 ppt) salinity regimes.